Rancang Bangun Sistem Informasi Penjualan Komputer Berbasis Website - Partono, Partono (Program Studi Teknik Informatika Universitas Pamulang, 2020)
There are several problems that arise in CV. X, in terms of service and sales methods, include sales transactions made only in places available in the company, limited service time because it is only done during working hours, and a lack of means of communication because orders made by telephone are constrained in providing a physical picture product. Therefore, the design of a website-based computer sales information system can make it easier to provide information to the wider community and also make it easier to make transactions at any time. The writing method used is descriptive method. While the development tool for designing this system uses a design tool in the form of Unified Modeling Language (UML). The diagrams used include: Use Case Diagrams, Sequence Diagrams and Class Diagrams and the development of this system uses PHP programming. Implementation of website-based computer sales system at CV. This X can make it easier for prospective buyers to access information about the company and about the products offered online, making it easier for prospective buyers to get the information needed to make it easier to make transactions online without depending on the company's location, can serve sales transactions without depending on company working hours.